A PV power supply module for a portable Cubesat satellite ground station - Mwanyasi, Gustave M.; Adonis, Marco (Journal of Energy in Southern Africa, 2014)
This research focuses on the problem of powering a remote and mobile satellite ground station, where utility power is unavailable. It focuses on the use of photovoltaic energy, which is now widely accepted as an alternative source of energy. However, PV suffers from low conversion efficiency, non-linear I-V characteristics, which depend on temperature changes and the earth rotation. The research focuses on accurate determination of the ground station power budget whose total power demand involves an azimuth and rotator function and a current which varies depending on the stages of communication with the satellite. The power budget is used to determine the size, the ratings of solar generators, batteries and the system components. With the aid of a power logger, the PV voltage, the battery voltage, the AC voltage and PV power output is analysed for varying satellite loads. The data is analysed by taking into account the solar irradiation level on the day of measurement and the percentage cloud cover. This method is found to improve the reliability and can be adopted to improve reliability of standalone PV systems. The results are vital in PV power management and design.